Impact of lesion size on photodynamic therapy with verteporfin of predominantly classic lesions in age related macular degeneration. Issue 3 (17th February 2005) - Arias, L; Pujol, O; Berniell, J; Rubio, M; Roca, G; Castillo, L; Acebes, E
Abstract : Aim: To determine if photodynamic therapy (PDT) outcomes are related to lesion size in patients with subfoveal predominantly classic choroidal neovascularisation (CNV) secondary to age related macular degeneration (AMD). Methods: According to greatest linear dimension (GLD) of the entire lesion determined with fluorescein angiography (FA) patients were divided into two groups. In the first group GLD was <3000 μm and in the second one GLD was 3000–5000 μm. All eyes were treated with standard PDT with the verteporfin protocol. The primary outcome was the proportion of eyes in both groups that did not show significant leakage in FA at the end of follow up. Secondary outcomes were changes in GLD and in best corrected visual acuity (BCVA). Results: 64 patients (mean (SD) age, 76.7 (7.7) years; range 58–95 years) were recruited to participate in the study. All participants in the study completed the follow up time (mean 16.6 months). 24 patients (75%) in the group of smaller lesions (n = 32) compared with 15 patients (46.8%) in the group of larger lesions (n = 32) did not show significant leakage in FA at the end of follow up (p = 0.02). A GLD increase >1000 μm was recorded in nine eyes (28.1%) in the group of smaller lesions and in 16 eyes (50%) in the group of larger lesions (p = 0.07). 22 eyes (68.7%) in the group of smaller lesions compared with 19 eyes (59.3%) in the group of larger lesions lost less than three lines of vision (p = 0.06). Relevant side effects related to verteporfin therapy were not recorded, except for four patients (6.2%) with infusion related back pain. Conclusions: These results suggest that lesion size at baseline may be a prognosis factor in PDT in patients with subfoveal predominantly classic CNV secondary to AMD. There are no relevant side effects or safety concerns derived from verteporfin therapy.